Evaluación del desarrollo sostenible y su influencia en el marco socioeconómico de la fundación Maquita - Almeida Basurto, Gema Andrea (2020)
The present investigation consisted of the evaluation of sustainable development and its influence in the socioeconomic framework of the Maquita Foundation. Located in Manabí Province of Portoviejo canton, for this, 4 phases were developed, the first one included Identifying the variables present in sustainable development to measure performance at the socioeconomic level. Unlocking a broad search that revealed the indicators that describe sustainable development in the socioeconomic framework through the selection of experts. The second phase was the determination of the current situation of the variables of sustainable development and the influence on the small producers associated with the Maquita Foundation, that is, that relevant data of the environment in which the organization operates was disclosed, identifying the problematic, we proceeded to design the questionnaire and apply the survey using the SSPS software, which allowed showing tables, and exposing effective results for taking a reliable analysis. Giving way to the third phase, which was to correlate the variables to define the influence of sustainable development within the socioeconomic level of the Maquita Foundation participants, using the Pearson test, each of the indicators was correlated, determining the reliability of sustainable development in the Maquita Foundation and what is the level of socioeconomic development of the affiliated organizations. And in this way of design, the last phase was the elaboration of an action plan that contributes to the actions of fair trade through the variables and indicators of sustainable development, which allowed managing each of the counterproductive situations to improve the quality of life and productivity of the organization.